Identifications Characteristics of Land and Water Users Along The Brantas Riverbanks - Rahadi, Bambang (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
Water supply and land along the Brantas Riverbanks should be functioned to conserve the river optimally. People behavior to land and water use affect their condition so that the users characteristics are important to be studied. This research was conducted to identify the characteristics of the land and water use activity and technique along the Brantas River.This research type is an explanatory research, using the data compiled from questionnaires that spreads to 3 zone categories (upstream, midstream and downstream). The sampling method is using Stratified-Classified Purposive Random Sampling. The Brantas riverbankâ€™s land and water user characteristics were farmers owned less than 0.25 Ha, monthly income range from 750000 to 1500000 rupiahs, and believed not to change the land function from farming at least for the next 10 years. Keywords:Â Brantas riverbanks, user identification, characteristics